EVALUATION OF SOME LIVER ENZYMES AND ALPHA-FETOPROTEIN IN WORKERS OCCUPATIONALLY EXPOSED TO E-WASTE IN NNEWI, ANAMBRA STATE NIGERIA - Abo, Isaac Kanu; Mbachu, Nancy Amara; Edet, Mark Matthew; Ezeugwunne, Ifeoma Priscillia; Ugwu, Nneka Mabel (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
BACKGROUND: The advent of electricity has spurred significant technological advancements, leading to the production of numerous electrical and electronic devices. This progress, however, has resulted in a surge of largely irreparable electronic waste (e-waste) being constantly shipped to Nnewi, a metropolitan city with large-scale commercial and industrialactivities. E-waste contains thousands of chemicals, many of which are toxic to humans upon exposure.AIM OF THE STUDY: To evaluate the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and serum levels of alpha-fetoprotein (AFP) in workers occupationally exposed to e-waste.METHODOLOGY: The study comprised 40 e-waste workers (exposed group) and 40 healthy individuals (control group). Approximately 5 ml of venous blood was collected from each participant. The liver enzymes – ALT, AST, and ALP were evaluated colorimetrically, while AFP was assayed by Enzyme-linked Immunosorbent Assay (ELISA) method. Data obtained was statistically analyzed using SPSS windows version 25 with significance set as p<0.05 at 95% confidence interval; Independent T-test, descriptive statistics and Pearson correlation were employed where relevant. Results were presented as means ± standard deviation in contingency tables.RESULT: There was no significant difference (p>0.05) in the activities of ALT, AST, ALP and serum level of AFP between the exposed subjects and the control. However, significantly negative correlation was found between age and ALT (r = -0.294; p= 0.024), while DOE also had negative correlation with ALP (r= -0.294; P= 0.024) - all among e-waste exposed group.CONCLUSION: This study has shown that exposure to e-waste may not have a harmful effect on the liver function, since there was no significant difference in the liver function enzymes, and serum levels of AFP. However, age and longer duration of exposure to e-waste could be detrimental to health.